SOME FACTORS AFFECTING THE GROWTH AND DEVELOPMENT OF YOUNG CHILDREN OF PRIMARY SCHOOL AGE (Scientific journal of the Fergana State University, 2025)
The article presents some factors affecting the growth and development of younger school-age children, their content, impact on the body, and the positive and negative results that occur or are expected in their organs and structures. It is intended for teachers of a wide range of general education schools, parents, and future bachelors and masters.